Effect of coexisting diabetes mellitus and chronic kidney disease on mortality of cirrhotic patients with esophageal variceal bleeding. Issue 1 (December 2016) - Lung, Chia-Chi; Jian, Zhi-Hong; Huang, Jing-Yang; Nfor, Oswald Ndi
Abstract Background Esophageal variceal bleeding (EVB) is a serious and common complication of cirrhosis. Diabetes mellitus (DM) and chronic kidney disease (CKD) increase mortality in patients with cirrhosis. However, whether coexisting DM and CKD increase mortality in cirrhotic patients with EVB remains unclear. Methods We enrolled cirrhotic patients hospitalized with the first presentation of EVB from 2005 through 2010 using Longitudinal Health Insurance Database 2005. The hazard ratios (HRs) of 42-day and one-year EVB mortality were calculated using Cox regression model. Results We identified 888 patients hospitalized with the first presentation of EVB. Among the cirrhotic patients with EVB, all-cause mortality at 42-day and one-year were 21.3 and 45.0 %, respectively. The respective HRs for the 42-day and one-year mortality were 1.80 (95 % confidence interval [CI], 1.10–2.97) and 1.52 (95 % CI, 1.06–2.17) for patients with CKD and 0.79 (95 % CI, 0.57–1.10) and 0.88 (95 % CI, 0.71–1.09) for patients with DM. Specifically, coexisting CKD and DM increased the 42-day and one-year mortality with respective HRs of 1.99 (95%CI, 1.03–3.84) and 1.84 (95%CI, 1.14–2.98) compared with those without CKD and DM. The HRs for 42-day and 1-year mortality in female patients with DM and CKD were 4.03 (95%CI, 1.40–11.59) and 2.84 (95%CI, 1.31–6.14) respectively, and were 2.93 (95%CI, 1.14–7.57) and 2.42 (95%CI, 1.28–4.57) in male patients with DM and CKD. Conclusion We identified that coexisting DM and CKD increased risk of mortality at 42 days and 1 year following EVB.